Implications of Supervision Effectiveness and Work Culture on Employee Performance with Work Motivation as an Intervening Variable - Suarni Norawati; Agusmanto Agusmanto; Zulher Zulher; Nurman Zakaria (Dinasti Publisher, 2025)
Achieving the SDGs (Sustainable Development Goals) targets and being linked to Minimum Service Standards (SPM), for this reason it is necessary to make efforts to improve health programs that touch directly to the community, equalize access and improve the quality of health services, develop health and management systems that are able to improve and developing health workers. To achieve all this, it is very necessary to have optimal employee performance. Therefore, it is necessary to know the factors that can influence employee performance, both direct and indirect influences. This research was conducted at the Kampar District Health Service which is located on Jalan DR. A Rahman Saleh No.22, Bangkinang, Bangkinang District, Kampar Regency City, Riau 28463. The aim of this research is to find out and analyze; 1) the influence of supervision on employee work motivation; 2) the influence of work culture on employee work motivation, 3) the direct influence of supervision on employee performance, 4) the direct influence of work culture on employee performance, 5) the influence of work motivation on employee performance, 6) the indirect influence of supervision on employee performance through employee work motivation and 7) the indirect influence of work culture on employee performance through employee work motivation. This research uses primary data and secondary data obtained by distributing questionnaires, interviews, documentation and research files. The population of this research was all employees at the Kampar District Health Service, totaling 85 employees and all of them were used as samples. The data analysis tool in this research uses the Structural Equation Modeling (SEM) model and in data processing the SmartPLS version 3.0 software is used, and hypothesis testing is carried out at an alpha of 5%. The results of this research conclude that 1) supervision has proven to have a significant effect on employee motivation; 2) work culture is proven to have a significant influence on employee work motivation, 3) direct supervision is proven to have a significant influence on employee performance, 4) work culture is not proven to have a significant influence on employee performance, 5) work motivation is proven to have a significant influence on employee performance, 6 ) indirect supervision is proven to have a significant effect on employee performance through work motivation and 7) work culture is indirectly proven to have a significant effect on employee performance through employee work motivation